Hsa_circ_0067997 promotes the progression of gastric cancer by inhibition of miR-515-5p and activation of X chromosome-linked inhibitor of apoptosis (XIAP) - Haibo Zhang; Xiumin Wang; Hongchun Huang; Yongfeng Wang; Fangfang Zhang; Shaofang Wang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Circular RNAs (circRNAs) have been revealed to play vital roles in modulating gene expression and participate in several pathological responses including gastric cancer (GC). However, the larger numbers of the circRNAs in GC progression remain undetermined. In the present study, four GC related circRNAs expression profiles from the Gene Expression Omnibus (GEO) database were enrolled. We identified hsa_ circRNA_00067997 (circ_0067997) as an oncogene in GC. qRT-PCR was used to validate the expression of circ_0067997 in GC tissues and cell lines. The results revealed that circ_0067997 was upregulated in GC, and high circ_0067997 expression was associated with the poor overall survival rate of GC patients. Knockdown of circ_0067997 significantly reduced cell viability, inhibited colony formation, and attenuated invasive ability, whereas overexpression of circ_0067997 exhibited opposed effects. Circ_0067997 was identified to be a sponge for miR-515-5p directly. Moreover, XIAP was demonstrated to be targeted and regulated by miR-515-5p. In conclusion, circ_0067997 was identified to be an oncogene in GC by regulating miR-515-5p/XIAP axis.